Novel multiple pooling and local phase quantization stable feature extraction techniques for automated classification of brain infarcts - Dogan, Sengul; Barua, Prabal Datta; Baygin, Mehmet; Chakraborty, Subrata; Ciaccio, Edward J.; Tuncer, Turker; Acharya, U. Rajendra (Elsevier, 2022)
This study aims to introduce a hand-crafted machine learning method to classify ischemic and hemorrhagic strokes with satisfactory performance. In the first step of this work, a new CT brain for images dataset was collected for stroke patients. A highly accurate hand-crafted machine learning method is developed and tested for these cases. This model uses preprocessing, feature creation using a novel pooling method (it is named P9), a local phase quantization (LPQ) operator, and a Chi(2)-based selector responsible for selecting the most significant features. After that, classification is done using the k-nearest neighbor (kNN) classifier with ten-fold cross-validation (CV). The novel aspect of this model is the P9 pooling method. The inspiration for this pooling method was drawn from the deep learning models, where features are extracted with multiple layers using a convolution operator applied to the pooling method. However, pooling decompositions have a routing problem. The P9 pooling function creates nine decomposed models, hence the name. The LPQ feature extractor is applied to images to generate sub-bands for feature generation. The Chi(2) selector is then employed to select the most significant features from the created feature vector, and these features are utilized for the classification using the k-nearest neighbor algorithm (kNN). The introduced P9-LPQ feature extraction-based learning model attained over 98% classification accuracy in all cases. The results obtained in this paper show that the proposed method can successfully classify stroke types. For this reason, the developed model can pre-diagnose stroke types in the future. (C) 2022 Nalecz Institute of Biocybernetics and Biomedical Engineering of the Polish Academyof Sciences. Published by Elsevier B.V. All rights reserved.
Keywords: LPQ; P9 pooling; Brain image classification; Computer vision; Chi2 selection; Hand-crafted features